2016
DOI: 10.1016/j.redox.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The hydroxypyridinone iron chelator CP94 increases methyl-aminolevulinate-based photodynamic cell killing by increasing the generation of reactive oxygen species

Abstract: Methyl-aminolevulinate-based photodynamic therapy (MAL-PDT) is utilised clinically for the treatment of non-melanoma skin cancers and pre-cancers and the hydroxypyridinone iron chelator, CP94, has successfully been demonstrated to increase MAL-PDT efficacy in an initial clinical pilot study. However, the biochemical and photochemical processes leading to CP94-enhanced photodynamic cell death, beyond the well-documented increases in accumulation of the photosensitiser protoporphyrin IX (PpIX), have not yet been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…This suggests that the iron chelator CP94 is most effective in the cancer cells where the haem biosynthesis pathway is more likely to be disrupted . These findings support several studies that found that the addition of an iron chelator to a PpIX precursor increased PpIX accumulation and therefore fluorescence before irradiation , with MAL + CP94 treated cells producing the greatest enhancement of PpIX fluorescence in tumor cells . This occurs because iron chelating agents reduce cellular levels of free iron, which is essential for haem formation to take place and thus this change in cellular environment, forces more PpIX to accumulate in the cell .…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…This suggests that the iron chelator CP94 is most effective in the cancer cells where the haem biosynthesis pathway is more likely to be disrupted . These findings support several studies that found that the addition of an iron chelator to a PpIX precursor increased PpIX accumulation and therefore fluorescence before irradiation , with MAL + CP94 treated cells producing the greatest enhancement of PpIX fluorescence in tumor cells . This occurs because iron chelating agents reduce cellular levels of free iron, which is essential for haem formation to take place and thus this change in cellular environment, forces more PpIX to accumulate in the cell .…”
Section: Discussionsupporting
confidence: 79%
“…PpIX is produced in the mitochondria, but it can subsequently localize within cell membranes and the cytosol , leading to apoptosis or necrosis respectively . We previously found that cell death following PDT resulted from low amounts of apoptosis but high amounts of necrosis, possibly as a result of huge mitochondrial damage . However, the main type of cell death following PDT is still to be established and heavily depends on the treatment parameters employed .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations